2012
DOI: 10.1007/s10456-012-9284-y
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells

Abstract: Endostatin, the C-terminal fragment of collagen XVIII, is a potent anti-angiogenic factor that significantly modulates the gene expression pattern in endothelial cells. Upon cell surface binding, endostatin can not only function extracellularly, but also translocate to the nucleus within minutes. However, the mechanism by which this occurs is partially understood. Here we systematically investigated the nuclear translocation mechanism of endostatin. By chemical inhibition and RNA interference, we firstly obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…Nucleolin, which is mainly located in the nuclei, can translocate to the cell surface when endothelial cells are stimulated by extracellular matrix and VEGF (32). When endostatin binds to cell surface nucleolin, both can be internalized and then translocated to the nuclei of endothelial cells (20,29,33). Here we found that adipogenesis stimulated nucleolin expression on the cell surface of differentiating 3T3-L1s at days 2, 4, and 6 of differentiation (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolin, which is mainly located in the nuclei, can translocate to the cell surface when endothelial cells are stimulated by extracellular matrix and VEGF (32). When endostatin binds to cell surface nucleolin, both can be internalized and then translocated to the nuclei of endothelial cells (20,29,33). Here we found that adipogenesis stimulated nucleolin expression on the cell surface of differentiating 3T3-L1s at days 2, 4, and 6 of differentiation (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Endostatin is cleaved from collagen XVIII, a core protein of heparan sulfate proteoglycan in vascular basement membranes, by proteases and metalloproteases such as elastase, matricillin, or cathepsin L that are produced by endothelial cells as a reaction to induced angiogenesis (3,8). Endostatin inhibits VEGF-induced endothelial progenitor cell (EPC) synthesis but also appears to interfere directly with endothelial nitric oxide synthase (eNOS) and targets upstream of its signaling pathway (23,29). The positive correlation between the number of injected CD34 + cells and endostatin levels could reflect this theory.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that endostatin has potent inhibitory effects on endothelial cell proliferation, migration, and tube formation [2,3] . Nucleolin, integrins, caveolin and clathrin have been demonstrated to mediate the anti-tumor effects of endostatin [4][5][6] . Except in endothelial cells, endostatin also has anti-tumor lymphangiogenic and anti-lymphatic metastasis functions [7][8][9] , further supporting the conclusion that endostatin is a potent anti-tumor drug with the potential ability to restrict tumor progression and metastasis [10] .…”
Section: Introductionmentioning
confidence: 99%